Analisis Strategi Pemasaran untuk Peningkatan Volume Penjualan Produk Kuliner Khas Korea Selatan (Studi Kasus pada Holdak Sorong) - Kastanya, Reyza Sherina Putri; Sapari, Lili S. J.; Maryen, Andrei (Attractive : Innovative Education Journal, 2022)
The purpose of this study is to analyze the marketing strategy that has been implemented by Holdak to increase its sales volume. In this study, it was analyzed using data collection methods, namely by observation, and interviews. Based on the results of the analysis that has been carried out by Holdak, it can be concluded that. Holdak's marketing strategy aims to introduce Korean food in Indonesia. Holdak also designs orders using attractive but still informative designs from social media such as Instagram, Facebook, WhatsApp and print media such as brochures and banners. Holdak has also developed a promotional mix in the form of sales promotions, internet marketing on social media, collaborated with various organizations such as Go-Food, and GrabFood, as well as conducting transactions through BCA and Mandiri EDC machines, and Shoppe and QRIS in order to make it easier in terms of payments, as well as helping in increasing sales volume Keywords: Analysis Marketing Strategy, Increasing Marketing, Selling Product Kuliner